ESTIMATION OF VOID SPACE STRUCTURE OF ZARICHNA AREA POOR-POROUS ROCKS BASED ON PETROPHYSICAL AND GEOPHYSICAL STUDIES - Bezrodna, I.; Shynkarenko, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The authors have conducted the investigation of rock samples and well logging data for the layers of Zarichna 3A well (located in Zarichna area of Dnieper-Donets basin) in order to estimate their prospectivity as poor-porous reservoirs of oil and gas on the basis of their void space structure studies. A set of petrophysical studies of gas-, oil- and water-saturated rocks was conducted at the petrophysical lab of the Institute of Geology including investigations under the alternating pressure conditions. Statistical analysis of density, electrical, filtration and storage, acoustic properties was done. Geophysical well logging data interpretation was performed using “Geopoisk” software. The database of well logs included the results of caliper, acoustic, electrical and radioactive logging. Assessment of void space structure on the basis of well logging and petrophysical data was conducted using the original method of inversion of acoustic investigations data into the structure of void space. This method is based on the least square method with use of both nonlinear optimization and conditional moment methods. During the standard analysis of petrophysical and geophysical well logging data total mismatch of conclusions was found: rocks determined as poor-porous reservoirs on the basis of well logging data did not show the same result for the petrophysical studies. Complex analysis of results of the acoustic properties measurements under the alternating pressure conditions made possible the qualitative analysis of rocks’ void space structure. Authors have made quantitative assessment of distribution of voids of different formats for the collection of core samples and rock layers. According to the petrophysical investigations data, it was found that void space of studied sandstones almost does not contain fracture-like voids, the void space of organogenic-detrital limestones consists mostly of granular and secondary voids, dolomite limestones include mostly fracturelike voids (0.71% - 0.95%). From the geophysical well logging data it was revealed that among the studied rock layers of well there are four carbonate layers which can be defined as perspective reservoir rocks with high fracture porosity. As a result of complex investigations it was found that studied interval of the well contains compacted poor-porous reservoirs presented mostly by fractured dolomite limestone. The perspective for the future studies of Zarichna area samples and similar areas is to extend current investigations by including anisotropy data which are planned to be measured in the Institute of Geology. The results of this work can be used for the determination of prospectivity of rocks with different lithology and complexity of void space during their petroleum potential studies.